No Clinical Benefit of Empirical Antimicrobial Therapy for Pediatric Diarrhea in a High-Usage, High-Resistance Setting. (26th September 2017) - Duong, Vu Thuy; Tuyen, Ha Thanh; Van Minh, Pham; Campbell, James I; Phuc, Hoang Le; Nhu, Tran Do Hoang; Tu, Le Thi Phuong; Chau, Tran Thi Hong; Nhi, Le Thi Quynh; Hung, Nguyen Thanh; Ngoc, Nguyen Minh; Huong, Nguyen Thi Thanh; et al.
Abstract : We identified high antimicrobial usage and high antimicrobial resistance in children hospitalized with bloody and/or mucoid bacteria-associated diarrhea. There was no clinical benefit of antimicrobial therapy in children with diarrhea; adequately powered randomized controlled trials are required. Abstract: Background: Pediatric diarrheal disease presents a major public health burden in low- to middle-income countries. The clinical benefits of empirical antimicrobial treatment for diarrhea are unclear in settings that lack reliable diagnostics and have high antimicrobial resistance (AMR). Methods: We conducted a prospective multicenter cross-sectional study of pediatric patients hospitalized with diarrhea containing blood and/or mucus in Ho Chi Minh City, Vietnam. Clinical parameters, including disease outcome and treatment, were measured. Shigella, nontyphoidal Salmonella (NTS), and Campylobacter were isolated from fecal samples, and their antimicrobial susceptibility profiles were determined. Statistical analyses, comprising log-rank tests and accelerated failure time models, were performed to assess the effect of antimicrobials on disease outcome. Results: Among 3166 recruited participants (median age 10 months; interquartile range, 6.5–16.7 months), one-third (1096 of 3166) had bloody diarrhea, and 25% (793 of 3166) were culture positive for Shigella, NTS, or Campylobacter . More than 85% of patients (2697 of 3166) were treated with antimicrobials; fluoroquinolones were the most commonly administered antimicrobials. AMR was highly prevalent among the isolated bacteria, including resistance against fluoroquinolones and third-generation cephalosporins. Antimicrobial treatment and multidrug resistance status of the infecting pathogens were found to have no significant effect on outcome. Antimicrobial treatment was significantly associated with an increase in the duration of hospitalization with particular groups of diarrheal diseases. Conclusions: In a setting with high antimicrobial usage and high AMR, our results imply a lack of clinical benefit for treating diarrhea with antimicrobials; adequately powered randomized controlled trials are required to assess the role of antimicrobials for diarrhea.